DIVERSITY OF POTENTIAL BACTERIA IN PADDY FIELD WITH NATURAL AND CONVENTIONAL FARMING SYSTEMS - Hadija, Hadija; Kuswinanti, Tutik; Jayadi, Muhammad; Larekeng, Sitti Halimah (Jurnal Agrotek Tropika, 2025)
One of the causes of the rising use of chemical inputs is the high index of rice farming in Indonesia. It constitute a few of the factors contributing to Indonesia’s declining rice fields’ quality. This study aimed to classify and identify the diversity of potential bacteria in the rhizosphere of rice plants. Methods this research used the enumeration method, biochemical test (bacteria characterization), and bacterial clustering. Further analysis of the clustering results is molecular identification to identify potential bacteria to the species level. The second location used a natural farming approach to calculate the amount of bacteria, the largest overall number of bacteria. The lowest number of isolates was obtained at a location with a conventional system. Thirty-two pure isolates were isolated from two rice fields in Sallasee Village, Bulukumba Regency. After clustering potential bacteria, six potential bacterial isolates were obtained in location two with natural farming systems. These bacteria are potential because they can fix nitrogen, dissolve phosphate, IAA, cellulosic enzymes, and catalase enzymes. Results Molecular species identification found three species of Bacillus Subtilis (LK.2.5, LK.2.12, and LK.2.1), also found two species of Brevundimonas with different species, namely (LK.2.13) isolate and Brevundimonas diminuta strain BZC3 isolate LK. 2.8. Meanwhile isolate LK.2.2 was identified as a Pseudomonas azotoformans strain S4. The similarity of identified bacterial species is between 97% - 99% with the Gen Bank data at NCBI. The functional ability of each bacterium varies greatly depending on the species and strain of each bacterium